Single-crystal X-ray diffraction, EMPA, FTIR and X-ray photoelectron spectroscopy study of narsarsukite from Murun Massif, Russia. (1st April 2017) - Schingaro, E.; Mesto, E.; Lacalamita, M.; Scordari, F.; Kaneva, E.; Vladykin, F. N.
A crystal chemical study of narsarsukite from the Murun alkaline massif, Russia has been carried out combining single-crystal X-ray diffraction, electron microprobe analyses, micro-Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The narsarsukite single crystals are tetragonal (space group I4/m) with unit-cell parameters: 10.7140(1) ≤ a ≤ 10.7183(2) Å and 7.9478(1) ≤ c ≤ 7.9511(1) Å. The XPS analysis showed that Fe occurs in the mineral as Fe3+, whereas the FTIR spectrum showed that the sample studied is anhydrous. The average crystal chemical formula of the Murun narsarsukite is: Na2.04K0.01(V5+0.01Ti0.74Zr0.01Al0.01Fe3+0.22Mg0.01)1.00Si4.00(O10.74F0.23OH0.03)11.00. Structural disorder at octahedral and interstitial sites was modelled and also discussed in consideration of the main substitutional mechanism Ti4+ + O2– ↔ Fe3+ + (F–, OH–) active in the structure of the mineral.